2013
DOI: 10.1111/ahe.12051
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Oxytocin, Vasopressin and Atrial Natriuretic Peptide and Their Modification in Rat Hypothalamic Paraventricular Nucleus During Resistance Training

Abstract: SummaryMany studies have demonstrated the physiological effects of oxytocin (OT), atrial natriuretic peptide (ANP) and vasopressin (VP) in the homoeostasis of body fluids during physical exercise. However, a little information is available about the related immunohistochemical changes in hypothalamic magnocellular neurosecretory system during and after the training. The aim of the present work was to study the immunohistochemical changes in OT, ANP and VP levels in the hypothalamic paraventricular nucleus duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Resistance exercise also regulates other hormonal outputs related to the HPA axis, namely oxytocin and vasopressin (Farina et al, 2014; Lipari et al, 2010). These studies have shown that ladder climbing produces a decrease in oxytocin-positive neurons in the paraventricular nucleus of the hypothalamus, indicative of either an increase in the release or decrease in the production of oxytocin in this region (Farina et al, 2014).…”
Section: Recent Advances In Resistance Exercise and Cns Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance exercise also regulates other hormonal outputs related to the HPA axis, namely oxytocin and vasopressin (Farina et al, 2014; Lipari et al, 2010). These studies have shown that ladder climbing produces a decrease in oxytocin-positive neurons in the paraventricular nucleus of the hypothalamus, indicative of either an increase in the release or decrease in the production of oxytocin in this region (Farina et al, 2014).…”
Section: Recent Advances In Resistance Exercise and Cns Activitymentioning
confidence: 99%
“…These studies have shown that ladder climbing produces a decrease in oxytocin-positive neurons in the paraventricular nucleus of the hypothalamus, indicative of either an increase in the release or decrease in the production of oxytocin in this region (Farina et al, 2014). Although resistance training does not produce immediate changes in vasopressin concentrations, increases in vasopressin-positive neurons are observed in the paraventricular nucleus following a 15-day rest period (Farina et al, 2014).…”
Section: Recent Advances In Resistance Exercise and Cns Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…CNP is also distributed widely in brain, but its level does not differ in each brain region [ 8 ]. In our previous studies showed in the developing rat that the ANP is present in the hypothalamic supraoptic [ 9 ], suprachiasmatic nuclei [ 10 ] and lateral choroid plexus [ 11 ], therefore also showed that ANP is involved in the resistance training, since in the hypothalamic supraoptic nucleus ANP-immunopositivity is lesser in the trained than the sedentary rats and the immunopositivity increases from 15th to 45th days of a resistance training with decreased release in bloodstream of the peptides, [ 12 ]; by contrast in the hypothalamic paraventricular nucleus the ANP-immunopositivity has no significant change [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ways in which exerciserelated myokines (exerkines) are involved in tissue crosstalk during physical exercise is a topic of interest and is likely to attract further research attention in the future. Exercise affects vasopressin and oxytocin expression in the neurons of the paraventricular nucleus (Farina et al, 2014) and induces a fivefold increase in the circulating levels of the neurohypophyseal hormone vasopressin (Melin et al, 1980). This increase is associated with the beneficial effects of exercise on muscle homeostasis and suggests a model whereby physical activity stimulates muscle secretion of the neurohypophyseal hormones, which increases muscle responsiveness to the same hormones through the up-regulation of their receptors (Adamo et al).…”
Section: Exercise Endocrinological Effectsmentioning
confidence: 99%